An Analysis of Denotation and Connotation in Chairil Anwar’s Poem (e-Journal of Linguistics, 2020)
This study primarily investigates denotative and connotative meaning inwords. Both of denotation and connotation are helpful for readers ofpoetry to find the interpretations and implied meaning. This analysisfocuses on meaning of words that was taken randomly from a poem.The data is analyzed descriptively using Griffith’s concept about threestages of interpretation, there are literal meaning, explicature andimplicature. The result shows that a word not only has denotation, butalso negative and positive connotation. Both of negative and positiveconnotations are possible that refer to an expression or a word. Themajor finding of the study is every word has one connotative meaningeither negative or positive.
Keywords: meaning; denotation; connotation; poem